Click inspired synthesis of p-tert-butyl calix[4]arene tethered benzotriazolyl dendrimers and their evaluation as anti-bacterial and anti-biofilm agents. (5th November 2020) - Agrahari, Anand K.; Singh, Ashish K.; Singh, Anoop S.; Singh, Mala; Maji, Pathik; Yadav, Shivangi; Rajkhowa, Sanchayita; Prakash, Pradyot; Tiwari, Vinod K.
Abstract : CuAAC inspired calix-[4]arene tethered benzotriazolyl dendrimers were developed and investigated for their therapeutic potential, where 7 displayed potent anti-bacterial and anti-biofilm activities against drug-resistant & slime producing organisms. Abstract : Calixarenes with their three-dimensional structural architecture and ease of functionalization at the upper and/or lower rim are well-known for their plethora of applications in chemical, physical, biological and other disciplines. Herein, CuAAC click inspired p-tert -butylcalix[4]arene tethered benzotriazolyl dendrimers, for example, N-1, N-2 type 2-fold compound 6 and 7 'G(0)' and 6-fold compound 16 and 17 'G(1)' generation benzotriazolyl dendrimer, were devised and also evaluated for their therapeutic potential both in vitro and in vivo . The developed calix[4]arene tethered benzotriazolyl dendrimers have been characterized by standard spectroscopic analysis including NMR ( 1 H and 13 C), MS, and SEC. Among all the benzotriazolyl dendrimers developed, compound 7 was identified as the effective one which provided potential anti-bacterial and anti-biofilm activities against drug-resistant and slime producing organisms without imparting cytotoxicity to the eukaryotic systems.